THE ROLE OF RECREATION IN DECREASING THE PSYCHOLOGICAL STRESS OF PUBLIC SCHOOL TEACHERS IN MAYSAN GOVERNORATE - Lech. Dr. Akram Hamid Karam (Proximus Journal Publishing, 2024)
The aim of the research the role of recreation in alleviating the psychological pressure of public school teachers in Maysan governorate, and the researcher used the descriptive method to suit the nature of the research, and the research community and its sample were public school teachers in Maysan governorate for the academic year (2022/2023), and the researcher built a psychological pressure scale for public school teachers in Maysan governorate and presented it to experts and used the appropriate statistical methods, The researchers presented, analyzed and discussed the results through its own table, and then the researcher wrote the conclusions that included the psychological pressure scale for teachers working in public schools with a high degree of reliability and stability, and through the scale it was reached to identify the psychological pressures suffered by teachers working in public schools and the role of recreation in reducing psychological pressures, as well as the most important recommendations to activate the role of recreation and recreational activities to face the psychological pressures of teachers during work, establish professional excellence incentives to encourage and motivate them to practice their work without pressure.
Keywords: Recreation; stress; public school teachers.